Dual (type IV) left anterior descending artery - Başkan, Özdil; Cengiz, Erkan; Yahya, Pamela (Alliance of Small Island States (AOSIS), 2013)
Congenital coronary artery anomalies are uncommon. Dual left anterior descending coronary artery (LAD) is defined as the presence of two LADs within the anterior interventricular sulcus (AIVS), and is classified into four types. Type IV is a rarely reported subtype and differs from the others, with a long LAD originating from the right coronary artery (RCA). Dual LAD is a benign coronary artery anomaly, but should be recognised especially before interventional procedures. With the increasing use of multidedector computed tomography (MDCT), it is essential for radiologists to be aware of this entity and the cross-sectional findings.
Keywords: Artery; Dual Left Anterior Descending; Type IV; Right Coronary Artery (RCA)